Antibiotic Resistance Profiling of Staphylococcus aureus Isolated from Clinical Specimens in a Tertiary Hospital from 2010 to 2012 - Juayang, Alain C.; de los Reyes, Gemma B.; de la Rama, April Joy G.; Gallega, Christine T. (Interdisciplinary Perspectives on Infectious Diseases, 2014)
MRSA infection can affect a wide array of individuals that may lead to treatment failure. Also, the infection has the potential to spread from one area to another particularly health care facilities or communities eventually causing minor outbreaks. With this premise, the study aimed to describe MRSA infections using the hospital-based data of a tertiary hospital in Bacolod City, Philippines, from 2010 to 2012. Specifically, this study aimed to evaluate the antimicrobial resistance of S. aureus isolated from clinical specimens and to put emphasis on the prevalence of MRSA and Inducible Clindamycin Resistance. A total of 94 cases from 2010 to 2012 were diagnosed to have S. aureus infection using conventional bacteriologic methods. From these cases, 38 (40.6%) were identified as MRSA and 37 (39.4%) were inducible clindamycin resistant. Wounds and abscesses were considered to be the most common specimens with MRSA infections having 71.05% while blood was the least with 5.3%. For drug susceptibility, out of the 94 S. aureus cases, including MRSA, 100% were susceptible to linezolid making it the drug of choice for this study. It was then followed by tetracycline having a mean susceptibility of 95%;, while penicillin G was ineffective with 94 cases having 0% susceptibility.